Noradrenergic neurotransmission within the bed nucleus of the stria terminalis modulates the retention of immobility in the rat forced swimming test - Nagai, Michelly M.; Gomes, Felipe V.; Crestani, Carlos Cesar [UNESP]; Resstel, Leonardo B.M.; Joca, Sâmia R.L. (Wolters Kluwer, 2013)
The bed nucleus of the stria terminalis (BNST) is a limbic structure that has a direct influence on the autonomic, neuroendocrine, and behavioral responses to stress. It was recently reported that reversible inactivation of synaptic transmission within this structure causes antidepressant-like effects, indicating that activation of the BNST during stressful situations would facilitate the development of behavioral changes related to the neurobiology of depression. Moreover, noradrenergic neurotransmission is abundant in the BNST and has an important role in the regulation of emotional processes related to the stress response. Thus, this study aimed to test the hypothesis that activation of adrenoceptors within the BNST facilitates the development of behavioral consequences of stress. To investigate this hypothesis, male Wistar rats were stressed (forced swimming, 15 min) and 24 h later received intra-BNST injections of vehicle, WB4101, RX821002, CGP20712, or ICI118,551, which are selective α1, α2, β1, and β2 adrenoceptor antagonists, respectively, 10 min before a 5-min forced swimming test. It was observed that administration of WB4101 (10 and 15 nmol), CGP20712 (5 and 10 nmol), or ICI118,551 (5 nmol) into the BNST reduced the immobility time of rats subjected to forced swimming test, indicating an antidepressant-like effect. These findings suggest that activation of α1, β1, and β2 adrenoceptors in the BNST could be involved in the development of the behavioral consequences of stress. © 2013 Wolters Kluwer Health | Lippincott Williams & Wilkins.
Keywords: adrenoceptors; bed nucleus of the stria terminalis; forced swimming test; noradrenaline; rat; stress; 2 (2 methoxy 1,4 benzodioxan 2 yl) 2 imidazoline; 2 [[2 (2,6 dimethoxyphenoxy)ethyl]aminomethyl] 1,4 benzodioxan; 3 isopropylamino 1 (7 methyl 4 indanyloxy) 2 butanol; 5 [2 [[2 hydroxy 3 [4 (1 methyl 4 trifluoromethyl 2 imidazolyl)phenoxy]propyl]amino]ethoxy]salicylamide; beta 1 adrenergic receptor; beta 2 adrenergic receptor; animal experiment; animal tissue; antidepressant activity; behavior change; controlled study; immobilization; limbic system; locomotion; male; neurotransmission; nonhuman; noradrenergic system; open field test; stria terminalis